Profil Gigi Tiruan Sebagian Lepas yang Dibuat di Jakarta - Laura Susanti Himawan (Journal of Dentistry Indonesia, 2015)
The profile of removable partial dentures in Jakarta is not known. This study was designed to collect information about the location of the missing teeth, the incidence of various classes, the type of the denture, and the mean number of teeth present, to compare with the study done in North America, West America, Germany, Sweden and Scotland. Data were collected from 3 large dental laboratories in Jakarta - secondary data. There were 148 models used for this study. Results indicated that like other countries, mandibular RPDs are more common than maxillary RPDs. According to the Kennedy classification, in Jakarta class III is the most common type of RPD, but in other countries, class I. The type of denture made for class II to replace on or two missing teth in Jakarta was mostly saddle denture. The mean number of teeth present in Jakarta and Germany showed the same result, lower more than the upper.